2003
DOI: 10.1038/sj.bjc.6600863
|View full text |Cite
|
Sign up to set email alerts
|

A role for BRCA1 in sporadic breast cancer

Abstract: To test the hypothesis that altered expression of BRCA1 protein may play an important role in sporadic breast cancer development, 50 randomly selected primary breast cancers (frozen sections, 5 years' median follow-up) were immunolabelled with two monoclonal BRCA1 antibodies (MS110 and MS13). MS110 labelling was exclusively nuclear showing no relation to outcome or tumour pathology. Western blotting demonstrated crossreactivity, suggesting antibody nonspecificity. MS13 labelling was predominantly cytoplasmic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
(29 reference statements)
0
29
0
Order By: Relevance
“…However, it is important to mention that some studies evaluating BRCA1 protein expression and prognosis have shown different results. For examples, Taylor et al [11] noted both nuclear and cytoplasmic staining in the majority of normal breast epithelium and lack of correlation between cytoplasmic staining and clinical features; Fraser et al [46] showed no relation to outcome or tumor pathology, however, in their study; MS110 (the antibody used in the current study) showed cross reactivity by Western blotting suggesting antibody nonspecificity.…”
Section: Discussionmentioning
confidence: 89%
“…However, it is important to mention that some studies evaluating BRCA1 protein expression and prognosis have shown different results. For examples, Taylor et al [11] noted both nuclear and cytoplasmic staining in the majority of normal breast epithelium and lack of correlation between cytoplasmic staining and clinical features; Fraser et al [46] showed no relation to outcome or tumor pathology, however, in their study; MS110 (the antibody used in the current study) showed cross reactivity by Western blotting suggesting antibody nonspecificity.…”
Section: Discussionmentioning
confidence: 89%
“…Staining was scored blind by two independent observers using a weighted histoscore method (Fraser et al, 2003), interclass correlation coefficients (ICCC) were calculated and confirmed acceptable correlation between observer scores (Armitage and Berry, 1995). ICCC values for histoscores were 0.67 (good) and 0.91 (excellent) for PSA and AR staining, respectively (Armitage and Berry, 1995).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 90%
“…Tissue staining intensity was scored blind by two independent observers using a weighted histoscore method (Fraser et al, 2003) also known as the Hscore system (McCarty et al, 1986). Histoscores were calculated from the sum of (1 Â % cells staining weakly positive) þ (2 Â % cell staining moderately positive) þ Table 1 shows the median histoscore and interquartile range (IQR) for hormone-sensitive tumours (HSPCs) and hormone-refractory tumours (HRPCs) and the P-values of HSPC histoscores compared to HRPC histoscores using a Wilcoxon signed-rank test.…”
Section: Immunohistochemistrymentioning
confidence: 99%